HUBUNGAN PERAWATAN LUKA PERINEUM PADA IBU NIFASDENGAN LAMA PENYEMBUHAN LUKA JAHITANPERINEUM IBU NIFAS DIRUANG LINGKUPBPM SANADAH, SST MOJOGENENGMOJOKERTO - Dwi Pratiwi, Yeni; Ma’rifah, Asirotul (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Many of postpartum mother do not know how to do the treatment of perineum as well. The consequence of incorrect perineal treatment for postpartum mother who suffered perineum wound could cause the delay of wound recuperation process. The purpose of this reseach was to determine the relationship of perineum treatment by long recuperation at BPM Sanadah Mojogeneng village, Mojokerto. The research design was analytic correlation by using cross sectional approachment. The population was all of postpartum mother who suffered perineum wound at BPM Sanadah Mojogeneng village, Mojokerto, the technique of sampling by the way of consecutive sampling and was gotten as many as 11 respondent who suffered perineum wound. The research variable was perineum treatment and long recuperation wounds seam. The data collection was done by questionnaire and observation. After collection then be done by data processing and continued with the statistic test of Spearman Rho by helping of SPSS 16.0 version. The results of this research which done precise wound treatment was 2 people (18,2%) with fast wound recovery was 2 people (18,2), imprecise wound treatment was 5 people with fast wound recovery was 1 person (9,1%) normal was 3 people (27,3%) long was 1 person (9,1%), imprecise woundtreatment was 4 people (36,4%) with normal wound recovery was 1 (9,1%) long was 3 people (27,3%). The results showed p (0,007) < α (0,05) so H0 was refused, it meant that there was a relationship between perineum wound treatment with wounds recuperation, with r = 0,759 that show the strong relationship. the incorret perineum treatment can infuence the wound recuperation process so that the wound can not be healed normally and could cause infection to postpartum mother that can cause the death of postpartum motherKey words: Perineum wound, The Way of Treatment, and Long Recuperat.